Correlation of Lifestyle and Gender with Hypertension Incidence - Dinasti, Thia Wulan; Rahayu, Sri (Jurnal Kesehatan, 2025)
Hypertension is a disease whose initial cause is unknown, therefore hypertension is called a silent killer. Factors suspected of causing hypertension come from unhealthy lifestyles. In addition, gender is also a factor that affects blood pressure. The purpose of this study was to determine the relationship between lifestyle and gender and the incidence of hypertension. This study used a quantitative method, with a cross-sectional design. This population is based on research from a preliminary survey at Dr. Moewardi Surakarta Hospital of 10,252 patients. A sample of 109 participants was obtained using a purposive sampling technique. Research data were collected using a lifestyle questionnaire to measure the level of the patient's lifestyle. Data analysis used univariate tests and bivariate chi-square tests. From the study results, a p-value of 0.012 (<0.05) was obtained, which means a relationship exists between lifestyle and the incidence of hypertension. For the gender variable, a p-value of 0.013 (<0.05) was obtained, which implies a relationship exists between gender and the incidence of hypertension. The majority of 86 participants (78.9%) had a moderate lifestyle category. This study also showed that women tend to be at risk of hypertension, namely 48 participants (44.0%) of 64 female participants suffered from hypertension. Lifestyle and gender are significantly related to the incidence of hypertension. Men and women need to increase their knowledge about healthy lifestyles to improve hypertension prevention.